TINDAK PIDANA MENDISTRIBUSIKAN GAMBAR PORNOGRAFI SECARA BERULANG KALI DALAM BENTUK INFORMASI ELEKTRONIK - Nafisha Maudyna; Setiyono (Fakultas Hukum Universitas Trisakti, 2022)
Pornography on the internet is used frequently to commit crimes against decency. The internet's convenience in this instance encourages someone to disseminate it frequently. The phrasing of the issue under discussion is the type of punishment meted out to those responsible for disseminating these pornographic photos via internet means. The research approach is normative; the research is descriptive in nature; secondary data are employed; secondary data are analyzed qualitatively; and deductive reasoning is used to derive conclusions. The findings of the investigation, the analysis, and the conclusion of the perpetrator's acts are in accordance with Article 45 Paragraph 1 in conjunction with Article 27 Paragraph 1 of the ITE Law along with Section 1 of Article 64 of the Criminal Code. The defendant acted in accordance with the terms of Article 45 paragraph 1 in connection with Article 27 paragraph 1 of the Information and Electronic Transaction Law in conjunction with Article 64 paragraph 1 of the Criminal Code when they regularly transmitted pornographic photos. The Criminal Code's (Article 64, Paragraph 1) regulations for continuous acts (Voorgezzete Handeling) must be taken into consideration while determining the appropriate punishment.